2008
DOI: 10.14429/djlit.28.4.196
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of HTML and Animated User Interfaces of an Online Exhibition

Abstract: The advancements in computer and telecommunication technologies have made the World Wide Web a vibrant place. Museums worldwide have recognised this phenomenon and are tapping the multimedia and interface technologies to present their contents online and in a more interesting manner. First priority to this is the user interface design and appropriate technologies to represent the contents. The paper discusses an animated interface created for an online exhibition with the Macromedia Flash software and compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…124 A popular analog exhibit may only exist in a single space, but for an online version, anyone with an adequate Internet connection may gain access, anytime, and from anywhere, including those unable to visit in person. 125 In Asia, online exhibits have been promoted as a way to instruct children increasingly disconnected from their culture and heritage due to the isolating nature of technology and the alienation from their parents who are frequently busy with work. 126 Well-made online exhibits are stimulating to both the mind and the senses; as such they make excellent tools for teaching and learning.…”
Section: Resultsmentioning
confidence: 99%
“…124 A popular analog exhibit may only exist in a single space, but for an online version, anyone with an adequate Internet connection may gain access, anytime, and from anywhere, including those unable to visit in person. 125 In Asia, online exhibits have been promoted as a way to instruct children increasingly disconnected from their culture and heritage due to the isolating nature of technology and the alienation from their parents who are frequently busy with work. 126 Well-made online exhibits are stimulating to both the mind and the senses; as such they make excellent tools for teaching and learning.…”
Section: Resultsmentioning
confidence: 99%
“…Users will generally wait about 10 seconds for a page to download, sometimes 15 seconds, before they lose interest 21 . In another study, it was found that Web users' tolerable waiting time for downloading webpages in information retrieval is approximately 2 seconds 22 . Almost half of the respondents (47 per cent) had accessed the sites from local area networks (LAN) both from NTU or their respective workplaces, and about (23 per cent) of them were using 56 Kbps connection.…”
Section: Speed Of Downloadingmentioning
confidence: 99%
“…Mobile technologies, which consist of Android, iOS and Windows, can facilitate the implementation of VR and digital exhibitions [ 10 ]. VR business applications are widely used in conferences and exhibitions such as desktop sharing, webcasts, 3D environments and multi-day conferences [ 13 ] to help people who have no time to be on-site or who are unable to attend [ 11 , 12 ]. AR-technology smart exhibition system based on digital devices enables visitors to obtain more detailed information [ 15 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…ICTs are indispensable to facilitate routine business tasks in conferences, exhibitions and shows [8]. Advanced technologies such as Web 2.0 [9], mobile technologies [10], Virtual Reality (VR) [11][12][13], Augmented Reality (AR) [14,15] are frequently used for users' feedbacks and experience in the conference and exhibition centers and virtual shows. In addition, Radio Frequency Identification (RFID) is widely applied for identifying and tracking users' location in the exhibitions [8,16].…”
Section: Introductionmentioning
confidence: 99%